Brand advertising and brand sharing of alcoholic and non‐alcoholic products, and the effects on young Thai people's attitudes towards alcohol use: A qualitative focus group study. (10th February 2019) - Kaewpramkusol, Ratchakorn; Senior, Kate; Nanthamongkolchai, Sutham; Chenhall, Richard
Abstract: Introduction and Aims: The dominant Thai alcohol companies have strategically employed brand advertising and brand sharing (using a very similar branding for both alcoholic and non‐alcoholic products) to circumvent restrictive alcohol advertising regulations. As empirical evidence confirms that exposure to alcohol advertisements increases youth drinking, young Thais could be at risk of constant and incidental exposure to alcohol advertising, hence leading to increased alcohol consumption. This study aims to explore young people's perceptions of these alcohol branding strategies and to examine how exposure to such advertising strategies affect their attitudes towards alcohol use. Design and Methods: Seventy‐two university students aged 20–24 years participated in 1.5‐h semi‐structured focus groups conducted in Bangkok and a peripheral province. Logos of two domestic alcohol brands were also used as part of projective techniques to elicit information. Thematic content analysis was used to analyse data. Results: Despite a range of alcoholic and non‐alcoholic products under the same branding, participants associated the logos primarily with beer—the flagship product. Branding strategies seemed to successfully increase young people's brand familiarity and affected their brand recognition and brand awareness. Participants had a high awareness of the alcohol companies' commercial activities but regarded alcohol advertisements to be indifferent to advertisements of other ordinary products. Discussion and Conclusions: Brand advertising is a dynamic tool that affects young people's attitudes towards the advertised brands and alcohol use. Due to early exposure to the brands, brand sharing increases brand familiarity and, among other factors, potentially affects drinking attitudes and purchase intentions.